1999
DOI: 10.2337/diacare.22.7.1084
|View full text |Cite
|
Sign up to set email alerts
|

Improved glycemic control reduces the impact of weight gain on cardiovascular risk factors in type 1 diabetes. The Epidemiology of Diabetes Complications Study.

Abstract: The prevalence of being overweight in type 1 diabetes remains lower than that in the general population. Moderate weight gain did not adversely affect the cardiovascular risk profile in the setting of improved glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
2
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 0 publications
8
51
2
5
Order By: Relevance
“…The finding that a higher baseline HbA1c predicted a larger and statistically significant increase in subsequent BMI in patients exposed to the twice-daily biphasic insulin dosage regimen when compared with the basal NPH plus prandial regular insulin regimen group in this study population was consistent with observations by Nansel et al, [10] Williams et al [11] and Conway et al [1] These researchers found that IIT and a higher baseline HbA1c were predictors of weight gain in patients in their respective settings. The current study also identified any insulin exposure adjusted for other covariates and baseline BMI to be significant predictors of weight gain in the cohort of patients observed.…”
Section: Researchsupporting
confidence: 81%
See 1 more Smart Citation
“…The finding that a higher baseline HbA1c predicted a larger and statistically significant increase in subsequent BMI in patients exposed to the twice-daily biphasic insulin dosage regimen when compared with the basal NPH plus prandial regular insulin regimen group in this study population was consistent with observations by Nansel et al, [10] Williams et al [11] and Conway et al [1] These researchers found that IIT and a higher baseline HbA1c were predictors of weight gain in patients in their respective settings. The current study also identified any insulin exposure adjusted for other covariates and baseline BMI to be significant predictors of weight gain in the cohort of patients observed.…”
Section: Researchsupporting
confidence: 81%
“…Conclusions can also be drawn that an increase in BMI is consistent with improvements in blood glucose control in this setting. Also, strategies already in place at the Kalafong Diabetes Clinic to control weight gain through advice on physical exercise, dietary and lifestyle counselling as part of clinical management should continue and be strengthened further to sustain optimal BMI outcomes in type 1 DM patients in this setting.The finding that a higher baseline HbA1c predicted a larger and statistically significant increase in subsequent BMI in patients exposed to the twice-daily biphasic insulin dosage regimen when compared with the basal NPH plus prandial regular insulin regimen group in this study population was consistent with observations by Nansel et al, [10] Williams et al [11] and Conway et al [1] These researchers found that IIT and a higher baseline HbA1c were predictors of weight gain in patients in their respective settings. The current study also identified any insulin exposure adjusted for other covariates and baseline BMI to be significant predictors of weight gain in the cohort of patients observed.…”
supporting
confidence: 81%
“…Therefore, it is possible that these individuals are at higher risk for the microvascular and metabolic complications of T1D and the macrovascular complications of T2D [18]. This is supported by investigations by Orchard et al [85,92], in the Epidemiology of Diabetes Complications Study, who reported that patients with T1D who have a positive family history of T2D were at greater risk for cardiovascular disease than those who did not. Furthermore, data from the Diabetes Control and Complications Trial (DCCT) show that weight gain and central obesity are associated with insulin resistance, hypertension, and dyslipidemia in T1D [93], and data from Epidemiology of Diabetes Interventions and Complications (EDIC) Study show that central obesity is an independent risk factor for incident microalbuminuria in individuals with T1D [94].…”
Section: Prognosissupporting
confidence: 67%
“…Furthermore, data from the Diabetes Control and Complications Trial (DCCT) show that weight gain and central obesity are associated with insulin resistance, hypertension, and dyslipidemia in T1D [93], and data from Epidemiology of Diabetes Interventions and Complications (EDIC) Study show that central obesity is an independent risk factor for incident microalbuminuria in individuals with T1D [94]. However, both DCCT and EDIC follow up studies show that intensive diabetes therapy results in a uniform, major reduction in (and significant protection from) microvascular disease [95], even in overweight or obese T1D patients [92]. Thus, there is the need to devise a consensus treatment regimen that would ensure the best glycemic and metabolic outcome for patients with double diabetes.…”
Section: Prognosismentioning
confidence: 99%
“…The protective effect of BMI change (i.e. an increase) is consistent with the intensification of insulin therapy and our previous report that weight gain in the presence of good glycaemic control is linked to an improved risk factor profile [27]. The underlying mechanism leading to the effect of change in HbA 1c on CAD risk, in the absence of a strong direct baseline association, is intriguing.…”
Section: Discussionmentioning
confidence: 60%